Relación entre conocimientos, hábitos y factores sociodemográficos para una alimentación saludable en adultos mayores de curgos, Perú - Bocanegra García, Sylvia Magali (2011)
Objective: The relation between the level of knowledge and the quality of the habits based on 10 steps for a healthy eating established for Peru, as well as the relation between both variables and some sociodemographic factors in elderly adults of the district of Curgos, La Libertad-Peru, was studied. Material and Methods: It was used a random sampling by conglomerates for the selection of 255 individuals, as well as a descriptive design to study the level of knowledge and the quality of the habits and correlational to study the relations between both variables and the considered factors. Data were collected by means of the structured interview and an interview guide, and analyzed by means of the correlation of Pearson and the chi square. Results: The 10-step knowledge average (0,74) was over the acceptable minimum value (0,66), whereas the habits quality average (0,59) was below this value. The level of knowledge of the 10 steps is acceptable in 86,67% of the elderly adults and the quality of the habits based on such steps is only acceptable in 18,82% of them. The correlation coefficient between the level of knowledge and the quality of the habits was 0,265, with p < 0,01. The source of information was associated with the level of knowledge, whereas the age with the quality of the habits, with p < 0,05. Conclusions: The correlation between the level of knowledge and the quality of the habits is positive, weak, and highly significant. The information source and the age are the only factors significantly associated with the level of knowledge and the quality of the habits in such population, respectively